2018
DOI: 10.1097/md.0000000000012202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the portage early education program on Chinese children with global developmental delay

Abstract: Children with global developmental delay (GDD) were trained with the Portage Guide to Early Education (PGEE) program.In the treatment group, the PGEE program was performed on children with GDD (45 cases) through a combination of family and hospital interventions, in a 1-to-1 ratio. The Gesell Infant Development Scale (GESELL) developmental quotient (DQ) and social adaptability were measured before and 6 months after PGEE implementation in the treatment group. These parameters were also evaluated in a control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…For example, a study in China on the effect of a portage early education program on children with GDD showed a significant positive change after six months of application. The program under evaluation is family-and hospital-based, meaning that it cannot be accurately compared with this study (Liu et al, 2018). In this study, an increase in general functioning measured by the CGAS was documented in both groups, but was more pronounced in the control group; however, the marked increase in the post-scores of the control group could also reflect the mothers' subjective responses.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…For example, a study in China on the effect of a portage early education program on children with GDD showed a significant positive change after six months of application. The program under evaluation is family-and hospital-based, meaning that it cannot be accurately compared with this study (Liu et al, 2018). In this study, an increase in general functioning measured by the CGAS was documented in both groups, but was more pronounced in the control group; however, the marked increase in the post-scores of the control group could also reflect the mothers' subjective responses.…”
Section: Discussionmentioning
confidence: 70%
“…A Brazilian study that focused on the evaluation of functional and developmental prognoses of children with GDD as they entered school found that 80% had their diagnosis changed within their first 3 years of life; their mother's age at birth, assistance to perform cognitive tasks and poor balance were determinant outcome factors (Dornelas et al, 2016). A Portage early education program for children with GDD in China succeeded in increasing their developmental quotient scores in gross and fine motor skills, adaptability, language and social abilities (Liu et al, 2018). Another study focused specifically on the improvement of social skills in children with GDD with or without developmental co-ordination disorder (Tal-Saban et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…GDS (Liu et al 2018) were compiled by A Gesell, an American psychologist, and revised twice in 1941 and 1980. It focused on five areas of abilitygross motor, fine motor, language, adaptability, and individual-social behavior, mainly for children with GDD aged from four weeks to six years.…”
Section: Standardized Measuresmentioning
confidence: 99%
“…However, research has since attempted to address the concerns raised by Brue and Oakl ( 2001 ). Both D. L. Cameron ( 2020 ) and Liu et al ( 2018 ) investigated the impact of the Portage approach compared with a control group and found the support had a positive impact on overall child development.…”
Section: Introductionmentioning
confidence: 99%